If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(6 + n) = -54 (6 * -9 + n * -9) = -54 (-54 + -9n) = -54 Add '54' to each side of the equation. -54 + 54 + -9n = -54 + 54 Combine like terms: -54 + 54 = 0 0 + -9n = -54 + 54 -9n = -54 + 54 Combine like terms: -54 + 54 = 0 -9n = 0 Solving -9n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '-9'. n = 0 Simplifying n = 0
| -4.3+(-9.3)= | | 3x^2y+5y=2x | | v=(3.14)(36)(16) | | 3(2x-1)-6(x-4)=-9 | | -8(1-2k)=8(k-3) | | 46+2=3(5x+1) | | (x^4)-(10x^3)+(21x^2)+40x-100=0 | | 5+16z-3=9z+93-6z | | 49-2x=9-7x | | 5a=2a+7 | | x=1.4-(1.2x) | | X+6.5=9.7 | | 5+3x=-2x | | -3+6v=3(3v+4) | | 4(5x+3)-5(2x+1)=27 | | 4x+9=40-3x | | 3(3x+1)=39 | | 6a=6a+7 | | -38-8x=-3(-6+5x) | | 4+12x=4+x | | 2x^2y+xy-100=0 | | 4+x=3x-2 | | 3.2+6=6m-15 | | 5m=8m-15 | | -(r-5-8p)= | | 4M+3M=12 | | 8(5+13x)-(-2x+8)=32 | | -7x+2.3=7x-7.9 | | -14-(-3)= | | -28+8x=4-6(2-2x) | | x^2+kx+(k+1)=0 | | 14(12k-12)+14(-10k-11)=42 |